KESAMAAN DAN KEMIRIPAN BAHASA-BAHASA KELOMPOK BIMA-SUMBA - Alex Djawa; Labu Djuli; Betharia Pane (Jurnal Lazuardi, 2026)
The similarity and similarity of language in the Bima Sumba Group languages ​​shows that there is a kinship relationship. This kinship relationship proves the divergence process. This process shows the durability, dissemination and inheritance of language that occurs naturally in the people of this group. This shows that there is retention and innovation in these languages. In all the languages ​​in this group, the same lexicon is found, meaning that inheritance is constant or retention and similar ones experience innovation. These similarities and similarities are not due to borrowing or coincidence. These similarities and similarities occur due to genetic factors or direct inheritance. Therefore, it can be said that through related languages, it can be said that humans are also related, only at different separation times.